Detecting the Limitations of Performance: Performance Art as a Neo-Shamanistic Ritual - Elif Dastarlı; İlkay Canan Okkalı (Sanat Tarihi Yıllığı)
Whilst numerous instances of performance art since the 1960s have propelled it into the realm of contemporary expression, articulating a precise academic definition for this art form rooted in its actions rather than in how the art is performed proves challenging. Detecting the limits of performance as a type of visual art is difficult because various theories (e.g., ritual studies, theatre theories) have linked performance art to ancient rituals, which complicates the delineation of performance within the visual art spectrum. Conversely, a yearning to reconnect with nature, which is lost in the modern milieu, has given rise to performances styled as neo-shamanist rituals. Examining whether performance art, which is conceived as a modern secular artistic production, has truly distanced itself from its ritualistic origins, particularly by scrutinizing instances where it aligns with shamanic rituals, is a viable avenue of exploration. This article seeks to cultivate an analytical and critical approach to performance art by delving into its ritualistic foundations to ascertain its position within the overarching concept of contemporary art. The study scrutinizes the connections of performance art with theatre, assesses Wagner’s proposition of Gesamtkunstwerk [total work of art], and unveils the contributions of avant-garde movements to the evolution of performance art. The article endeavors to provide a categorical definition of performance art as a genre wherein the method and form dictate the relationship between content and narrative. In this context, the article uses performance exemplars to examines the linguistic expressions of artists well-versed in Shamanism who identify as neo-shamans and draw inspiration from research into pagan religions. This exploration reveals the role of performance art in the resurgence of new age beliefs.